La columna lingüística de Juan B. Selva en "La Obra" (1923-1927) - Lidgett, Esteban (Pontificia Universidad Católica del Perú, 2023)
This paper addresses the linguistics column that Juan B. Selva published in the pedagogical journal La Obra between 1923 and 1927, with the aim of examining both the criteria of authority regarding linguistic knowledge, as well as the ideological assessments and attitudes expressed by the author in relation to the linguistic phenomena he describes. The analysis of the column (which was published in a context in which Argentina was witnessing the institutionalization of linguistics and the expansion of debates on language in the press) allows us to corroborate the centrality of normative issues, a characteristic feature of the genre. However, it also reveals the emergence of a discourse that rejects prescriptive positions and, instead, seeks scientific explanations for the linguistic phenomena it records.

Este trabajo aborda la columna lingüística que Juan B. Selva publica en la revista pedagógica La obra entre 1923 y 1927, con el objetivo de examinar tanto los criterios de autoridad en torno al saber lingüístico como las valoraciones ideológicas y las actitudes que el autor manifiesta ante los fenómenos lingüísticos que describe. El análisis de la columna, publicada en un contexto en el que se asiste en la Argentina a la institucionalización de la lingüística y a la expansión de los debates sobre la lengua en la prensa, permite corroborar la centralidad que asume la cuestión normativa, rasgo característico del género, pero también la emergencia de un discurso que rechaza la posición prescriptiva y que busca, en cambio, explicaciones científicas de los fenómenos lingüísticos que registra.
Juan B. Selva’s Linguistics Column in "La Obra" (1923-1927)
Keywords: Linguistics column; Argentina; Pedagogical press; Juan B. Selva; Columnas lingüísticas; Argentina; Prensa pedagógica; Juan B. Selva; https://purl.org/pe-repo/ocde/ford#6.02.06